S22 Analysis of the lung microbiome in human asthma using whole genome shot-gun metagenomics. (14th November 2013) - Hinks, TSC; Handley, S; Keller, B; Droit, L; Staples, KJ; Smith, C; Howarth, PH; Virgin, HW; Gadola, SD; Djukanovic, R
Abstract : Introduction and Objectives: Evidence is accumulating for the presence of bacteria in the airways and the existence of a commensal airway microbiome. Molecular techniques reveal complex microbial assemblages in bronchiectasis and COPD, but little is known about the airway microbiome in asthma or in health. Immunopathology in asthma may be driven by bacteria or fungi or even by chronic viral persistence. We undertook an analysis of the entire respiratory microbial metagenome in airway samples from carefully phenotyped subjects across a spectrum of asthma and health. Methods: 55 subjects (9 mild asthmatics, 16 moderate asthmatics, 15 with severe neutrophilic asthma without bronchiectasis and 15 healthy controls) underwent detailed clinical and immunological phenotyping, sputum induction, and bronchoscopy during periods of clinical stability. Protected bronchoalveolar lavage (BAL) and induced sputum were analysed by whole genome shot-gun sequencing for RNA and DNA from bacterial, viral and fungal genomes. Data were analysed using the VirusHunter analysis pipeline. Results: We found no evidence of novel viral species or of persistent viral infection. Protected BAL samples typically contained 500–5000 bacterial reads for organisms typical of the oral cavity or upper respiratory tract, consistent with microaspiration rather than a distinct airway microbiome. Bacterial abundance was not increased in asthma. Hierarchical cluster analysis revealed no general association between disease and the presence of bacteria, with the exception of two individuals with severe neutrophilic asthma in whom single pathogenic species were detected with high abundance. In the first subject, chronic Haemophilus influenzae infection was present, correlating with standard culture and a striking Th17 cell response in BAL. Specific antibiotic treatment resulted in a dramatic clinical improvement. In the second individual Tropheryma whipplei was present, and correlated with the presence of foamy macrophages and a deficiency of BAL Th17 cells. Conclusions : : The data from this study argue against the existence of a distinct airway microbiome in health or in asthma, but rather that lung microbes are a result of microaspiration. Conversely, in specific cases chronic low grade infection may drive immunopathology in asthma. It remains to be seen whether very severe forms of asthma have a more prominent microbiome.